Book Review The Leiden Legacy: Concepts of Law in Indonesia - Salampessy, M. Yahdi (UI Scholars Hub, 2014)
The Indonesian civil law system is often taken for granted, when it is actually a product of “institutional transplantation” and inherited from the Dutch Colonization. Long before the arrival of colonial powers in Indonesia several centuries ago, many local communities had operated within their self-regulating systems with multiple political entities. When colonization came to power, however, there was a massive shift from judge-made law to a centralized statute-based legal system imposed by the colonial order.